Exploring Layers of Meaning in the Poem “Kepada Noor” by Moch. Syarip Hidayat: A Semantic Study - Muhammad Darda Diyaulhaq; Rohanda Rohanda; Dedi Supriadi (Gunung Djati Conference Series, 2026)
This study aims to examine the layers of meaning in the poem “Kepada Noor” by Moch. Syarip Hidayat through a semantic perspective. Specifically, this research seeks to address how lexica/denotativel, connotative, and metaphorical meanings are constructed within the linguistic structure of the poem to understand the poet's linguistic strategies in expressing his inner experiences. The method employed in this research is descriptive qualitative. The approach utilized is semantic analysis, which scrutinizes linguistic units ranging from words and phrases to sentences. The analysis is conducted by identifying lexical and grammatical meanings as a foundation, which is then expanded to the analysis of connotative meanings, conceptual metaphors, and semantic coherence between stanzas to uncover deeper figurative meanings. The results conclude that the poem “Kepada Noor”: constructs meaning through the utilization of simple diction laden with natural symbolism, such as the metaphors of birds and nests, as well as the personification of the concept of longing. The research finds that the meaning within this poem is a conceptualization of emotional and spiritual experiences, where the repetition of sounds and words serves to reinforce the intensity of longing. Thus, the semantic approach proves effective in revealing the psychological and aesthetic dimensions of meaning hidden behind the structural text of this poem.